PubChem BioAssays 1063: A Poorly Exploited Source of New Antileishmanial Compounds - Sergio Sifontes-Rodríguez; Susana Meneses-Gómez; Alma Reyna Escalona-Montaño; Daniel Andrés Sánchez-Almaraz; Ofelia Pérez-Olvera; Aranza Regina Cañón Rosas; Pedro Zuriel Cruz Bautista; María Magdalena Aguirre-García (Journal of Parasitology Research)
PubChem Bioassays (AID 1063) reported the in vitro testing of 196,141 compounds against Leishmania major promastigotes. Although these results have been publicly available since 2008, limited efforts on further testing of some of these compounds has been published. The aim of the present work was selecting a small set of compounds that were highly active in that primary assay and assessing their antileishmanial activity in vitro and in vivo. Selected compounds were 100% active in the primary assay at 10 μM, were not theoretically toxic, did not have structural features of pan assay interfering substances, had positive druglikeness, and were not cytotoxic, and their activity rate in previous assays reported in PubChem Bioassays was under 5%. Seven commercially available compounds were purchased and tested against L. major, Leishmania mexicana, Leishmania amazonensis, and Leishmania infantum promastigotes; in mouse peritoneal macrophages (cytotoxicity); and against L. mexicana intracellular amastigotes. Eventually, four compounds with appropriate selectivity and high activity against L. mexicana amastigotes were tested by intralesional route (1%, 20 μL) in a mouse model of cutaneous leishmaniasis. Four compounds were active (IC50<10 μM) against the promastigote stage of the four Leishmania species tested. These four compounds were also active (IC50<10 μM) in vitro against intracellular amastigotes and in vivo in mice experimentally infected with L. mexicana. Results demonstrated the potential of these compounds as antileishmanials and the high, unexploited potential of AID 1063 as a source of new antileishmanial agents.